Impact of electrokinetic remediation of heavy metal contamination on antibiotic resistance in soil - Hongna Li; Yunlong Tian; Liu, Wen; Long, Yujiao; Jing Ye; Binxu Li; Na Li; Mengmeng Yan; Changxiong Zhu (Chemical Engineering Journal, 2020)
Electrokinetic remediation is an effective technology for soil contaminated with heavy metals. However, little is known about the fate of antibiotic resistance in the process under heavy metal stress, since antibiotic resistance genes (ARGs) are widely distributed and can be co-selected with heavy metals. This study focused on antibiotic resistant bacteria and ARGs over different remediation periods (1, 2, and 5 days), voltages (0.4 and 0.8 V cm−1), and initial concentrations (250–1,000 mg kg−1 for Cu, and 1,000–3,000 mg kg−1 for Zn). The application of polarity-reversal maintained a suitable pH, eliminating possible negative effects on soil quality. In addition to a decrease in total metals, the speciation was modified as residual forms decreased while reactive forms increased. Compared with anti-oxytetracycline bacteria, anti-sulfamethoxazole bacteria were more resistant to the electric field, which might be ascribed to greater constraints on their resistance enzymes. The presence of heavy metals accelerated the spread of ARGs, with a 2.67-fold increase for tetG, and a 3.86-fold increase for sul1. Among the ARGs studied, tetM and tetW, as well as sul genes were more easily removed than tetC and tetG genes. Finally, a significant correlation was found between ARGs and Cu, consistent with the relatively stronger toxicity of Cu and its high potential to induce the SOS response. This study advances the understanding of how electrokinetics influences antibiotic resistance in soil with heavy metals, which has important implications for the simultaneous control of these pollutants in soil.
Keywords: Anti-OTC bacteria; Anti-SMX bacteria; ARGs; Cu fractions; Zn fractions